Risk Management Literacy Level among Oil Palm Smallholders in Malaysia - Abdullah, Mohd Hafizuddin Syah Bangaan; Azmi, Amira; Yakob, Rubayah; Redzuan, Hendon (Jurnal Manajemen Hutan Tropika, 2024)
Risk management literacy is very important in influencing an individual's decision-making when taking preparatory steps to handle the anticipated risks. This includes oil palm smallholders who are constantly exposed to various types of risks. Therefore, this study aims to analyze the level of risk management literacy among oil palm smallholders in Malaysia. The data of the study was obtained from the online questionnaires distributed to oil palm smallholders using a random sampling method. The data obtained from the final sample of 200 smallholders were analyzed to examine the level of risk management literacy among palm oil smallholders using mean score analysis. The results found that the risk management literacy level among oil palm smallholders in Malaysia is at a moderately high level. Furthermore, mean score for the preference of saving instead of expenditure was the highest i.e. 4.40, indicating that smallholders possess high awareness on the importance of saving as one of the tools for risk management. The study’ findings allowed relevant authorities to formulate new programs such as training and awareness campaign of risk management, on continuous basis. It could assist smallholders to prepare for any potential risks and subsequently be able to create sustainable sources of income.